IMPLEMENTASI POJOK MINI MARKET DALAM MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENDORONG BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR. - Qomariyah, Titik Nur; Siti Inganah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problems raised from this study are How to apply the Problem-Based Learning (PBL) learning model using the Mini Market Corner media in mathematics learning in grade V of elementary school and How the use of the Mini Market Corner in the Problem-Based Learning (PBL) learning model can improve the critical thinking skills of mathematical grade V students of elementary school. While the purpose of this study is to describe the application of the Problem-Based Learning (PBL) learning model using the Mini Market Corner media in mathematics learning in grade V of elementary school. And to find out the increase in critical thinking skills of mathematical grade V students of elementary school through the use of the Mini Market Corner in the Problem-Based Learning (PBL) learning model. This study used a descriptive qualitative research type. While the research subjects used in this study were a mathematics teacher and 3 students of grade V MI Al-Mursyidah Mancilan Mojoagung Jombang. Data collection techniques are observation, interviews and documentation. Data reduction, data presentation and drawing conclusions and verification. The results of this study are This media is able to create an active, fun, and contextual learning atmosphere. Students are directly involved in the learning process through simulations of buying and selling activities that are relevant to everyday life, making it easier to understand mathematical concepts. And students' critical mathematical thinking skills have increased after the implementation of Problem-Based Learning (PBL)-based learning with Pojok Mini Market media. The increase can be seen from students' abilities in interpreting problems, analyzing information, evaluating alternative solutions, and putting forward logical reasons in solving problems. This learning provides space for students to develop high-level thinking skills meaningfully through real and collaborative learning experiences.